NUCB2 nesfatin-1 alterations in children with and without Helicobacter pylori Gastritis - Ugras, M.; Aydin, S.; Asik, G.; Akoluk, A.; Bicer, S.; Bicer, A. (Wiley-Blackwell, 2016)
[Abstract Not Available]
29th International Workshop on Helicobacter and Microbiota in Inflammation and Cancer -- SEP 15-17, 2016 -- Magdeburg, GERMANY